Legal and Ethical Studies in Medical Dispute Resolution from the Perspective of Judicial Medicine - Mubarak, Haikal; Miliyandra, Miliyandra; Priyanto, Eka; Respati, Gilang; Hernawati, Hernawati (PT FORMOSA CENDEKIA GLOBAL, 2025)
The resolution of medical disputes is becoming increasingly important in the context of the increasing number of cases that occur, both in court and out of court. This demands an in-depth understanding of the legal and ethical aspects involved in each stage of the dispute resolution process. The collection of data and statistics from various sources is an integral part of this study, as it will be the main foundation in providing an accurate and comprehensive picture of the complexity of the problem. The results of this study are expected to make a significant contribution to the development of legal policy and medical practice in Indonesia, so as to create a safer and fairer environment for all parties involved in the medical dispute resolution process. This will certainly have a positive impact on improving the existing health system, so that the public can get proper protection and justice in every aspect of medical services provided.